2013
DOI: 10.1007/s10508-013-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Sexual Behaviors Among Non-Commercial Men Who Have Sex with Men at Different Venues

Abstract: The prevalence of HIV infection among men who have sex with men (MSM) has increased rapidly in China. Previous studies suggested that some venue-specific characteristics could significantly affect MSM's sexual behaviors that were related to HIV transmission. Thus, to compare the HIV infection rates and related risky sexual behaviors among MSM at different venues, we conducted a cross-sectional study with time-location sampling in Shenzhen, China. Among the 801 MSM recruited in the study, 7.0 % (n = 56) were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…MSM-selling had higher prevalence of unprotected anal intercourse and recreational drug use. As suggested by Zhao et al, sexual risk behaviors among MSM may be influenced by venue-specific characteristics [28]. MSM-selling might use different websites to seek male sex partners and have different perception of online seeking, which might increase their HIV risk or facilitate HIV/STIs transmission.…”
Section: Discussionmentioning
confidence: 99%
“…MSM-selling had higher prevalence of unprotected anal intercourse and recreational drug use. As suggested by Zhao et al, sexual risk behaviors among MSM may be influenced by venue-specific characteristics [28]. MSM-selling might use different websites to seek male sex partners and have different perception of online seeking, which might increase their HIV risk or facilitate HIV/STIs transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In our TLS survey, the majority of MSM were recruited from low-end venues (parks, recreational centers or saunas) where quick and unsafe sex often occurs. Previous studies of Chinese MSM have revealed that MSM who attend these lowend venues are often more marginalized, e.g., who tend to be older, less educated and more likely to be married and identify themselves as non-gay (Zhao et al, 2013). Finally, different from TLS, RDS uses social networking in the recruitment process.…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of countries, MSM who were recruited via Internet were younger, better educated, had more sexual partners, and/or engaged in more condomless anal sex [22][23][24], while those recruited from traditional venues were less likely to use illicit drugs and were more likely to know the HIV status of their sexual partners [25]. However, findings vary by geographic location and source of sampling.…”
Section: Introductionmentioning
confidence: 99%